The Cooling Effect Estimation of Green Space Area Using an Empirical Approach in IPB Darmaga Campus - Sobri Effendy; Ahmad Sururi (Agromet, 2017)
Green space area has contributed to increase atmospheric condition in surrounding area. Here we would like to test the cooling effect of small green area located in IPB campus Darmaga. We monitored air temperature at the morning (6 am) and afternoon (2 pm) for period March-June 2013 in three different sites in campus. Totally, we collected 658 observed data. Our results showed that partial shade area (PSA) and site were the most influenced factors that contributed to the cooling effect. It appears that the cooling effect was found until a distance of 50 m from each monitoring site.  The cooling effect varied among sites, but it is consistent that the maximum effect occurred during afternoon. Our analysis confirmed that PSA has contributed to the cooling effect until 28%. Other factors that contributed to the cooling effect were vegetation characteristics and geometric configuration of the canopy. Further, our findings revealed that greenspace area is valuable to minimize high temperature effect from traffic street.